2020
DOI: 10.3389/fcimb.2020.571088
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Properties and Temporal Analysis of the Interaction of an Invasive Escherichia albertii With Epithelial Cells

Abstract: Diarrhea is one of the main causes of infant mortality worldwide, mainly in the developing world. Among the various etiologic agents, Escherichia albertii is emerging as an important human enteropathogen. E. albertii promote attaching and effacing (AE) lesions due to the presence of the locus of enterocyte effacement (LEE) that encodes a type three secretion system (T3SS), the afimbrial adhesin intimin and its translocated receptor, Tir, and several effector proteins. We previously showed that E. albertii stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…However, cathepsin B specific inhibitor, CA-074, did not affect the viral entry into the cells (Ou et al 2020 ; Pišlar et al 2020 ). This indicated that cathepsin L has a more important role in the SARS-CoV-2 expression (Pišlar et al 2020 ; Gomes et al 2020 ). Moreover, the expression of cathepsin L is associated with the extracellular matrix's degradation and was found significantly higher during chronic inflammation, a key attribute of SARS-CoV-2 infection (Gomes et al 2020 ).…”
Section: Human Cellular Receptors As Targets Of Coronavirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cathepsin B specific inhibitor, CA-074, did not affect the viral entry into the cells (Ou et al 2020 ; Pišlar et al 2020 ). This indicated that cathepsin L has a more important role in the SARS-CoV-2 expression (Pišlar et al 2020 ; Gomes et al 2020 ). Moreover, the expression of cathepsin L is associated with the extracellular matrix's degradation and was found significantly higher during chronic inflammation, a key attribute of SARS-CoV-2 infection (Gomes et al 2020 ).…”
Section: Human Cellular Receptors As Targets Of Coronavirusesmentioning
confidence: 99%
“…This indicated that cathepsin L has a more important role in the SARS-CoV-2 expression (Pišlar et al 2020 ; Gomes et al 2020 ). Moreover, the expression of cathepsin L is associated with the extracellular matrix's degradation and was found significantly higher during chronic inflammation, a key attribute of SARS-CoV-2 infection (Gomes et al 2020 ). The X-ray crystallographic studies indicated that the calpain inhibitors II and XII, GC-376 analogs: UAWJ246, UAWJ247, and UAWJ248, showed dual inhibition properties by inhibiting both M pro and cathepsin L (Sacco et al 2020 ).…”
Section: Human Cellular Receptors As Targets Of Coronavirusesmentioning
confidence: 99%
“…It is interesting to note that in E. albertii, another invasive pathogen that harbors the PAI LEE, the expression of the LEE regions also differed from that identified in the present study. In the E. albertii strain 1551-2, there was no difference in the expression of any of the evaluated genes ( ler, escJ, escV, escN, eae, and espA ) at 1.5 h, 3 h, and 6 h post-infection (22), while all genes but espA showed an increase on gene expression at 24 h post-infection (22). This comparative and complex scenario perhaps indicates that the expression of the LEE genes can be differentially regulated in different isolates, and perhaps this fact can lead to differences in their virulence potential.…”
Section: Discussionmentioning
confidence: 99%